The lure of the modern : writing modernism in semicolonial China, 1917-1937 - Shih, Shu-mei, 1961- (Berkeley series in interdisciplinary studies of China, 2001)
Shu-mei Shih's study is the first book in English to offer a comprehensive account of Chinese literary modernism from Republican China. In The Lure of the Modern, Shih argues for the contextualization of Chinese modernism in the semicolonial cultural and political formation of the time.